2011
DOI: 10.3174/ajnr.a2594
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Reduced Posterior Corpus Callosum Size in a Population-Based Sample of Young Adults Born with Low Birth Weight

Abstract: BACKGROUND AND PURPOSE:Several studies suggest that VLBW is associated with a reduced CC size later in life. We aimed to clarify this in a prospective, controlled study of 19-year-olds, hypothesizing that those with LBWs had smaller subregions of CC than the age-matched controls, even after correcting for brain volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…We have previously shown that this population of ex-prematures did not have a smaller total area of corpus callosum than the control group (27), but a significantly smaller posterior third of corpus callosum. Other authors have shown that isolated ventricular dilatation without other brain pathology is not associated with neuroimpairment (24,28).…”
Section: Discussionmentioning
confidence: 57%
“…We have previously shown that this population of ex-prematures did not have a smaller total area of corpus callosum than the control group (27), but a significantly smaller posterior third of corpus callosum. Other authors have shown that isolated ventricular dilatation without other brain pathology is not associated with neuroimpairment (24,28).…”
Section: Discussionmentioning
confidence: 57%
“…C), one ROI is defined in the midsagittal slice. The ROI is placed around the posterior third of the CC containing the splenium [Aukland et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic diseases are caused by a combination of exogenous and inherited factors. Acquired structural CC abnormali- Stewart et al, 1999;Nosarti et al, 2004;Andersen et al, 2006;Kontis et al, 2009;Aukland et al, 2011Glass et al, 2008 Normal aging Reduced size Ryberg et al, 2008;Griebe et al, Tomimoto et al, 2004;DiPaola et al, 2010Hensel et al, 2002Yamauchi et al, 2000 Traumatic brain injury Reduction in fractional anisotropy, reduced size…”
Section: Exogenous Factors (Table 4a and 4b)mentioning
confidence: 99%